1982
DOI: 10.1002/neu.480130303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of novel central and peripheral connections between molluscan central neurons in organ cultured ganglia

Abstract: An in vitro organ culture system for buccal ganglia of the adult snail, Helisoma, is described. The system supports: (1) maintenance of characteristic electrophysiological parameters of identified neurons over seven days of culture; (2) choline metabolism including uptake and synthesis over the same duration; (3) sprouting and growth of neurons in response to axotomy; (4) the formation of novel central electrotonic connections between identified neurons as a result of sprouting and growth. These observations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…No unusual electrical connections were found in this study, although they have previously been reported in molluscan ganglia (Cohan et al, 1987;Hadley et al, 1982). These 'incorrect' electrical connections are rather common in culture of the isolated cells (Bodmer et al, 1984;Carrow and Levitan, 1989;Hadley et al, 1983;.…”
Section: Growth Restrictions For Moto-and Interneuronscontrasting
confidence: 58%
See 2 more Smart Citations
“…No unusual electrical connections were found in this study, although they have previously been reported in molluscan ganglia (Cohan et al, 1987;Hadley et al, 1982). These 'incorrect' electrical connections are rather common in culture of the isolated cells (Bodmer et al, 1984;Carrow and Levitan, 1989;Hadley et al, 1983;.…”
Section: Growth Restrictions For Moto-and Interneuronscontrasting
confidence: 58%
“…In some cases new processes of neurons follow the routes of their original axons (motoneuron B15 in Aplysia (Ross et al, 1994), giant serotoninergic cerebral cell in Achatina (Chiasson et al, 1994) and in Helisoma (Murphy et al, 1985)). In other cases the neurons can produce aberrant branches (RPeD1 cell in Lymnaea , buccal neurons in Helisoma (Murphy and Kater, 1980a,b;Bulloch and Kater, 1982;Hadley et al, 1982), motoneurons in cockroach (Denburg, 1982)), although some predominant growth directions were observed. The neurons mentioned above originally grow into peripheral nerves and their behavior is similar to that of motoneurons in Clione.…”
Section: Growth Restrictions For Moto-and Interneuronsmentioning
confidence: 96%
See 1 more Smart Citation
“…2 A, arrow) can result in the formation of novel interneuronal connections during regeneration (Hadley et al, 1982). The commissure connecting the right and left buccal ganglia contains the axonal processes of many neurons, including those of 19 and 110.…”
Section: Synaptic Connections Between 19 and 110 Form During Regeneramentioning
confidence: 99%
“…Neurons from Aplysia (Bodmer et al, 1988;Carrow and Levitan, 1989), Lymnaea (Janse et al, 1986;Hamakawa et al, 1999a,b;Woodin et al, 1999), the leech (Ready and Nicholls, 1979;Nicholls et al, 1990;Fernandez-de-Miguel and Drapeau, 1995;De-Miguel, 2000;Kristan et al, 2001), and our system, Helisoma trivolvis (Hadley et al, 1982(Hadley et al, , 1985Kater, 1985;Zoran et al, 1996;Magoski and Bulloch, 1998) have been used extensively for the study of both electrical and chemical synapse formation between identified neurons in vivo and in cell culture.…”
Section: Introductionmentioning
confidence: 99%